Solvent-induced synthesis of hollow structured Fe3O4-based anode materials for high-performance Li-ion batteries - Zhikang Liu; Zhenghui Zhao; Shan Wang; Chuanxi Xiong (Journal of Materiomics, 2020)
High capacity Fe3O4-based anode materials have attracted a great deal of attention as an alternative to commercial graphite in Li-ion batteries (LIBs). However, it is still a challenge to alleviate the fast capacity fading of Fe3O4 due to the intercalation of Li+. In this work, we develop a novel and effective strategy to rapidly fabricate the hollow Fe3O4 nanostructures via the solvent-induced effect. The influence of the ratio of the tert-butanol (TB) and the water on the microstructure was further discussed. As expected, when the hollow nanostructures based on the 1:1 ratio of TB and water is used as the anode material for LIBs, a high reversible capacity of 1020 mA h g−1 after 100 cycles at 1 A g−1 and 450 mA h g−1 even for 5 A g−1 after 1000 cycles can be obtained, paving a new avenue to fabricate the functionally hollow nanostructures for high-performance anode materials or other applications.